The Influence of Role Models on Immigrant Self-Employment: A Spatial Analysis for Switzerland - Giuliano Guerra; Roberto Patuelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
Theoretical and empirical research suggests a connection between the presence of role models and the emergence of entrepreneurs. Existing entrepreneurs may act as role models for self-employment candidates by providing successful examples. By explicitly considering the self-employment rates of the natives, which may influence locally the decisions of immigrants towards entrepreneurship, we develop a simple model that explains immigrant self-employment rates for a sample of 2,490 Swiss municipalities. In addition, we accommodate for the presence of spatial spillovers in the distribution of rates, and test a spatial autoregressive model which takes into account the average self-employment rates of immigrants living in nearby municipalities. Our evidence shows a significant (positive) effect of such spatial network effects, which are characterized by a quick distance decay, suggesting spatial spillovers at the household and social network level. Additionally, we show that local conditions and immigrant pool characteristics differ, with respect to self-employment choices, when examining separately urban and rural contexts.
Keywords: C21; J24; J61; O15; R13; 330